Differential Gel Electrophoresis (DIGE) Evaluation of Naphthoimidazoles Mode of Action: A Study in Trypanosoma cruzi Bloodstream Trypomastigotes. - Giselle Villa Flor Brunoro; Vitor Marcel Faça; Marcelle Almeida Caminha; André Teixeira da Silva Ferreira; Monique Trugilho; Kelly Cristina Gallan de Moura; Jonas Perales; Richard Hemmi Valente; Rubem Figueiredo Sadok Menna-Barreto (Public Library of Science (PLoS), 2016)
BACKGROUND:The obligate intracellular protozoan Trypanosoma cruzi is the causative agent of Chagas disease, a neglected illness affecting millions of people in Latin America that recently entered non-endemic countries through immigration, as a consequence of globalization. The chemotherapy for this disease is based mainly on benznidazole and nifurtimox, which are very efficient nitroderivatives against the acute stage but present limited efficacy during the chronic phase. Our group has been studying the trypanocidal effects of naturally occurring quinones and their derivatives, and naphthoimidazoles derived from β-lapachone N1, N2 and N3 were the most active. To assess the molecular mechanisms of action of these compounds, we applied proteomic techniques to analyze treated bloodstream trypomastigotes, which are the clinically relevant stage of the parasite. METHODOLOGY/PRINCIPAL FINDINGS:The approach consisted of quantification by 2D-DIGE followed by MALDI-TOF/TOF protein identification. A total of 61 differentially abundant protein spots were detected when comparing the control with each N1, N2 or N3 treatment, for 34 identified spots. Among the differentially abundant proteins were activated protein kinase C receptor, tubulin isoforms, asparagine synthetase, arginine kinase, elongation factor 2, enolase, guanine deaminase, heat shock proteins, hypothetical proteins, paraflagellar rod components, RAB GDP dissociation inhibitor, succinyl-CoA ligase, ATP synthase subunit B and methionine sulfoxide reductase. CONCLUSION/SIGNIFICANCE:Our results point to different modes of action for N1, N2 and N3, which indicate a great variety of metabolic pathways involved and allow for novel perspectives on the development of trypanocidal agents.